STRATEGIZING IN THE MANAGEMENT OF MARKET CAPITALIZATION OF CORPORATE AGRICULTURAL ENTERPRISES - SUSLIKOV, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The essence of strategizing in the management of market capitalization of corporate agricultural enterprises has been studied. It has been shown that the strategy of managing the market capitalization of a corporate agricultural enterprise is a component of the overall economic strategic policy for sustainable development of the company. It has been determined that the purpose of the strategy is maximizing the market capitalization of the enterprise, and the strategic goal is to ensure a sufficient amount of capital for socio-economic, environmental and production development. The principles of strategy are systematic, transparent, competent, efficient and planned adaptability. The subjects of market capitalization management of corporate agricultural enterprises are top management and financial management of the corporation, underwriters and shareholders. The objects of market capitalization management have been defined as shares and their rates, dividends, investment risks, value of company assets, financial results, capital, corporate image, etc. The separation of financial and non-financial goals in the strategy of market capitalization management have been substantiated, which follows from the establishment of target strategic parameters for maximizing the market value of an enterprise and ensuring its sustainable development. The financial, administrative and legal methods of strategic market capitalization management have been allocated. The main stages of strategizing in the management of market capitalization include analysis of the state of development of a corporate enterprise, definition of mission and vision, setting goals and objectives, development of substrategies for managing the value of the units of an agricultural corporation, implementation of strategy, monitoring and reasonable adjustment of strategic goals and plans. It has been shown that the instruments and levers of strategic management of market capitalization of corporate agricultural enterprises are underwriting, corporate financial management and strategic marketing.
Keywords: strategizing; strategy; market capitalization; corporate agricultural enterprises; strategic financial management